THE DEVELOPMENT OF UZBEK THEATRE TERMINOLOGY IN THE 20th CENTURY - Zumriniso Kozimova (American Journals Publishing, 2023)
This article discusses the introduction, distribution and scope of use of theatre and modern theater terms into the Uzbek language. It will be possible to observe that these terms are directly related to the activities of the Jadids.
Keywords: trickery room, trickster, auditorium, imitator, spectacle, curtain, theatre, drama, stage.